On the relationship between globalization and income inequality: Does institution matter?. Issue 2 (14th September 2020) - Osode, Oluwanbepelumi E.; Iheonu, Chimere O.; Dauda, Risikat
Abstract : The purpose of the study is to examine the impact of globalization and institutional quality on income inequality as well as examining the influence of institutional quality on the relationship between globalization and income inequality. The study employed instrumental variable quantile regression which accounts for simultaneity/reverse causality. This method enabled us to determine how the existing level of income inequality affects the impact of globalization and institutions on income inequality. Findings revealed that the impact of globalization on income inequality depends on the measure of globalization utilized, while the impact of institutional quality on income inequality depends on the initial level of income inequality. More precisely, we found that trade globalization significantly reduces income inequality in the presence of improved institutional quality in countries where the initial levels of income inequality are low, while it increases income inequality in the presence of improved institutions in countries where the initial levels of income inequality are high. Furthermore, in the presence of improved institutional quality, foreign direct investment and official development assistance (financial globalization) significantly increase income inequality in countries where the initial levels of income inequality are high and low, respectively. Policy recommendations based on these findings are discussed.